New Approaches to the Analysis of Jihadism Online and Offline - Lohlker, Rüdiger (Studying Jihadism - Band 001, 2011)
Jihadism has been an important issue of public discussions since 9/11. Internet media have been used by Jihadis as means of communication, propaganda, recruitment, and even training purposes. In this volume, the processes of interaction on Jihadi internet sites are analysed. Particular attention lays on the mechanisms of spread of propaganda via the internet by diverse technical means. The process of transformation of Islamic knowledge into Jihadi knowledge, the rhetorics of videos, the development of South Asian Jihadi organisations and some conceptual issues are discussed.